Study of Factors and Relationships Shaping the Inclusion Prospects for LGBT Society: A Perspective Across Middle-Sized IT Enterprises in National Capital Region: Life Sciences - Tandon, Lochan Sharma; Agarwal, Dr. Priyanka; P. Joshi, Dr. Bhavesh (International Journal of Life Science and Pharma Research, 2023)
LGBT society and their employee rights and call for inclusion and embedment across the organizational ecosystem marks a revolutionary change in organizational working in IT companies in India. The need to explore the theoretical basis for the relationship between the organization and workplace-driven attributes and the respective generalization of the ’diversity management and inclusive culture’ construct is rampant. There is a growing realization that inclusive, integrative, and embedded LGBT personals often lead to wholesome and seamless business performance irrespective of sexual orientation and gender complexities. This study investigates the elements and linkages that impact LGBT societal inclusion chances inside middle-sized IT firms in the National Capital Region. Organizations are becoming more conscious of the significance of fostering an inclusive workplace for all workers, including those who identify as lesbian, gay, bisexual, or transgender (LGBT). This study investigates the numerous elements that contribute to or impede LGBT inclusion, the links between these factors, and the overall prospects for LGBT persons in middle-sized IT firms. The research was conducted for seven to eight months across the chosen unit of analysis in a defined and phased manner. The research above was conducted across the time ranging from May 2021 to February 2022 across the 438 mid-career employees in permanent charge across IT organizations in North Indian perspective. The industrial locations were selected to offer coverage to the aspects that essentially determine and shape the decision-making across the industrial cities of NCR. The research observed the significant impact of identity-conscious programs, ’identity-blind programs,’ ’age inclusiveness,’ ’awareness,’ and ’internal communications’ on ’workplace diversity’ and ’workplace inclusion’ across the LGBT society.